Culture as a Language Skill in FLT: Case-Study Master Students at Department of English at Chlef University - Chaal, Houaria (جامعة حسيبة بن بو علي الشلف - مخبر تعليمية اللغات وتحليل الخطاب, 2024)
ترتبط الثقافة باللغة برباط وثيق. إذ تعد اللغة الوسيلة الجوهرية في نقل الثقافة بمعتقداتها وقيمها ومعاييرها. فتعلم لغة أجنبية يعني بالضرورة تعلم ثقافتها. ولذلك، كثيرا ما وقفت الثقافة كعائق في تدريس اللغة لكل من الأساتذة والمتعلمين. على اعتبار أن المحتوى الثقافي الذي يدرس في أقسام اللغة يتأثر بمدى الاختلافات بين الثقافة الأم والثقافة الأجنبية. وبصفة عامة، أثناء تدريس اللغة، غالبا ما يتم التركيز على تطوير المهارات الأساسية الأربع. ومع ذلك، كثيرا ما يشير معلمو اللغة إلى الثقافة باعتبارها مهارة خامسة. ومن ثم، كانت الثقافة دائما حاضرة في عملية اكتساب لغة أجنبية. ولكن ماذا تعني هذه المهارة وكيف يجب تضمينها في عملية التعليم والتعلم؟ ما هي المواد التعليمية المصممة لتدريس عناصر الثقافة؟ بناء على ذلك، تسعى هذه الورقة إلى دراسة وضع تدريس الثقافة في قسم اللغة الإنجليزية بجامعة الشلف. باعتماد منهجية الملاحظة، اختارت الباحثة طلبة الماستر لمناقشة بعض التوصيات الواردة في حصص تدريس الأدب الذي يعتبر صورة ثقافية للأمم ومرآة عاكسة للمجتمعات، قصد التفكير مليا في ماهية المحتوى المثالي الذي يقوم عليه تدريس هذه المهارة. Culture and language are highly related. Language is the primary vehicle of culture since it conveys its beliefs, values and traditions. Therefore, learning a foreign language necessitates learning its culture. Accordingly, the status of culture in language teaching has always been a challenging issue for both teachers and learners. The cultural content taught in language classes may also be impacted by the extent of differences between the native and the target cultures. Generally, language teaching is based on the four skills acquisition. However, language teachers often refer to culture as a fifth skill. Hence, culture has always been present in the FLT class. But what does this skill imply and how should it be included into the teaching–learning process? What are the teaching materials designed for the cultural elements teaching? In this regard, this paper seeks to examine the status of teaching culture in ELT in the Department of English, at Chlef University. To conduct this study, the researcher chose Master students, depending on the class observation and discussion, in order to discuss some of the recommendations stated in the literature courses since literature is usually viewed as a cultural portrait of nations and communities. It reflects on what the ideal content of a course related to the teaching of this skill should be.
Keywords: المهارات اللغوية -- الثقافة اللغوية -- طلبة الدراسات العليا